Geographic distribution and time trend of human exposure of Di(2-ethylhexyl) phthalate among different age groups based on global biomonitoring data. (January 2022) - Qu, Jingyu; Xia, Wei; Qian, Xi; Wu, Yongning; Li, Jingguang; Wen, Sheng; Xu, Shunqing
Abstract: Despite being restricted by many authorities, di (2-ethylhexyl) phthalate (DEHP) is still widely detected in the environment and biospecimens. To indentify populations of high risk and evaluate the effects of DEHP restrictions, we elucidated the geographic distribution of DEHP exposure levels among pregnant women and different age groups, and compared the time trend of exposure levels with the time course of productions/restrictions. The estimated daily intake (EDI) was calculated based on biomonitoring data in published epidemiological studies, and then the group EDI (EDIG ) was calculated for one particular population, region, or period by weighting EDIs by sample sizes. Overall, 144, 965 samples from 45 nations were included, with the sampling time ranging from 1982 to 2017. Children had the highest exposure level (5.50 μg/kg bw/day) worldwide, while infants and pregnant women had low levels (2.13 and 1.89 μg/kg bw/day, respectively). The EDIG s varied considerably between countries, and the majority of corresponding hazard quotients were less than 1; however, the risk behind can not be ignored. In the general population, the DEHP exposure level showed a downtrend from 4.40 μg/kg bw/day before 2000 to 2.23 μg/kg bw/day in 2015–2017. In the European Union, the annual trend of DEHP EDIG s of children and adults fitted the production and consumption volume, and the EDIG s decreased more sharply in children. The EDIG s of children decreased with a delay along with the regulations on the use of DEHP. Cutting productions/consumptions and restrictions are effective to reduce DEHP exposure, but current efforts are far from enough on a worldwide scale. Highlights: Children usually suffer from higher DEHP exposure levels. The distribution of DEHP exposure levels varies between and within countries. The DEHP exposure levels show a downtrend since 1982 in the general population. Production and restrictions have impacted the DEHP exposure of target populations.